Reflecting on the integration of physiological systems: Evaluation of a didactic sequence based on the three pedagogical moments (Research, Society and Development, 2021)
Considering the relevance of working on the contents of physiology, exploring elements that lead students to understand the functioning of the human organism and homeostasis the objective of this work was to evaluate the opinion of high school students on the structure, application and effectiveness of a Didactic Sequence (SD) exploring the integration of physiological systems, thus seeking to sensitize the school community regarding health, attitudes and behaviors , enabling the exercise of criticality through the process of questioning, formalization of concepts and production of knowledge. The Three Moments Pedagogical approach was used. In the first moment, dynamics and contextualized questions involving the selected themes were used. In the second moment, dialogic classes, conversation circles and reading of scientific materials about the physiological systems explored in class were developed. During the third moment, the practice of "checking heart rate and saturation" was carried out. At the end of the application of the SD, the students answered a questionnaire, which aimed to evaluate the activities developed. The results obtained through the assessment tools demonstrated the potentialities of the proposed DS, and the relevance of working with the physiological systems in an integrated manner, in order to enable students to understand the functioning of the human body in a meaningful way.